The role of botulinum toxin in multimodal treatment of spasticity in ambulatory children with spastic cerebral palsy: Extensive evaluation of a cost-effectiveness trial - Johannes B.J Bussmann; Robert F. Pangalila; Henk J. Stam; Fabienne Schasfoort (Medical Journals Sweden, 2020)
A cost-effectiveness trial (the Space Bop study) on the added value of botulinum toxin injections (BoNT-A) in the leg muscles, as part of a multimodal intervention for ambulatory children with spastic cerebral palsy in the context of a single distinct cycle of care was performed recently by our group. For a broad set of effect outcomes, we found that BoNT-A had no added value if children received comprehensive rehabilitationHowever, this counterintuitive finding was met with scepticism. Since several noteworthy facts and experiences were recorded during the course of the trial and the dissemination phase, the aim of this paper was to describe and discuss some crucial aspects of, and barriers to, the Space Bop study, related to context and perspective, design and results, as well as publication and implementation. This paper discusses 5 issues: () the design, interpretation and presentation of previous research; () the role of one's own clinical experience and interpretation; () the aims of (BoNT-A) treatment; () conflict of interest, role of industry, and the role of history; () optimal treatment modalities and dose-response relationships. Despite the unambiguous findings from the Space Bop study, several factors hindered acceptance of the results. Awareness of these factors is important when performing rehabilitation research and disseminating and implementing research findings.